Learners’ Interpretation of Geometric Concepts in the Intermediate Phase: The Case of Limpopo Province - Jojo, Zingiswa (DIRASAT: EDUCATIONAL SCIENCES, 2016)
Geometry in primary schools contributes to helping learners to develop the skills of visualization, critical thinking, intuition, perspective, and problem-solving. These later culminate to formation of conjectures, deductive reasoning, logical argumentation and proof. This article reports on an exploratory study conducted with 219 grade 5 learners from 20 randomly selected primary schools in the Seshego district of Limpopo province of South Africa. The quantitative approach dealt with assessment of understanding of grade 4 mathematics concepts learnt as prescribed by Continuous Assessment Policy Statement (CAPS) for grade 5 learners at the beginning of the year 2014. The article reports only on the understanding displayed in responses to five out of twelve questions that sought interpretation of geometric concepts in the questionnaire. A follow up qualitative approach in which interviews were conducted with six learners on the basis of their responses to gain more insight into how they constructed their geometric meanings was conducted. Results indicated that some learners did not understand the questions but would respond to questions based on a word or diagram that they associated with a particular concept. Nonetheless, 99% of the 219 learners displayed understanding and familiarity with the concept of similarity. However the interpretation in other questions could be explained from the use of African languages that were used in the learners’ previous grades.